2023
DOI: 10.1186/s40359-023-01065-x
|View full text |Cite
|
Sign up to set email alerts
|

School bullying victimization and post-traumatic stress symptoms in adolescents: the mediating roles of feelings of insecurity and self-disclosure

Abstract: Background Posttraumatic stress symptoms (PTSSs) is known to be a typical problem for school bullying victims. However, the underlying mechanism between school bullying victimization and PTSSs remains unknown. This study examined the mediating roles of feelings of insecurity and self-disclosure in the relationship between school bullying victimization and PTSSs in adolescents. Methods Self-report questionnaires were used to assess 5013 adolescents;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Hypothesized relationships between rumination, distress disclosure, perceived social support, and PSG. (60,61). The DDI comprises 12 items and is designed to gauge the extent to which an individual feels at ease discussing personally distressing information with others (62).…”
Section: Distress Disclosure Indexmentioning
confidence: 99%
“…Hypothesized relationships between rumination, distress disclosure, perceived social support, and PSG. (60,61). The DDI comprises 12 items and is designed to gauge the extent to which an individual feels at ease discussing personally distressing information with others (62).…”
Section: Distress Disclosure Indexmentioning
confidence: 99%
“…The affect-regulation model of NSSI states that NSSI is a maladaptive coping style to deal with adverse emotions caused by the experiences of victimization. 33 For instance, adolescents who are bullied at school can experience a series of negative feelings, such as tension, frustration, and fear, 34 , 35 which may lead adolescents to implement NSSI to release emotional stress. 36 Several empirical studies also demonstrate that NSSI is more common among adolescents with experiences of bullying victimization compared to adolescents without such experiences.…”
Section: Introductionmentioning
confidence: 99%
“… 41 For the majority of adolescents, bullying victimization is deemed a traumatic experience. 35 In such circumstances, alexithymia symptoms may emerge as a negative reaction to the pressure induced by bullying victimization and can be interpreted as a psychological coping mechanism by which teenagers attempt to suppress negative feelings triggered by bullying victimization. A positive association between bullying victimization and alexithymia has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying-a power domination behaviour by an individual or group to intentionally harm others either physically or emotionally over a period-is a social problem that is affecting children in all parts of the world [1][2][3][4][5][6][7][8][9]. Globally, almost one in three students (32%) are bullied by their peers at least once every month [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a strong association between school bullying victimisation and adverse health risks of mental, psychosocial, and behavioural problems as well as later life performance [7,8]. Bullying, as a violent and oppressive behaviour, causes harm, and, therefore, provides a powerful moral imperative for particular attention within social work education and intervention [9].…”
Section: Introductionmentioning
confidence: 99%